THE EFFECT OF CHICKEN MANURE AS ORGANIC MATTER AND NPK FERTILIZER ON GROWTH AND YIELD OF CABBAGE IN ALLUVIAL SOIL - Tanti Hidayah, Nikmatun; Warganda, Warganda; Anggorowati, Dini (Fakultas Pertanian Universitas Tanjungpura, 2022)
Cabbage Flowers are flower buds in large numbers forming thick and dense circles. Utilization of alluvial soil as a growing medium is faced with low soil fertility, acidic soil pH, low levels of organic matter availability, and lack of nutrient content. The limited carrying capacity of the alluvial soil needs to be overcome by adding organic matter and nutrients needed to improve soil fertility as a growing medium for cauliflower plants. This study aims to determine the interaction of chicken manure as organic matter and NPK on the growth and yield of flower cabbage on alluvial soil. This research was conducted at Jalan Daya Nasional, Tanjungpura University Lecturer Complex, Pontianak from 27 December